1997
DOI: 10.1091/mbc.8.12.2379
|View full text |Cite
|
Sign up to set email alerts
|

RanGTP Targets p97 to RanBP2, a Filamentous Protein Localized at the Cytoplasmic Periphery of the Nuclear Pore Complex

Abstract: RanBP2, a protein containing FG repeat motifs and four binding sites for the guanosine triphosphatase Ran, is localized at the cytoplasmic periphery of the nuclear pore complex (NPC) and is believed to play a critical role in nuclear protein import. We purified RanBP2 from rat liver nuclear envelopes and examined its structural and biochemical properties. Electron microscopy showed that RanBP2 forms a flexible filamentous molecule with a length of ∼36 nm, suggesting that it comprises a major portion of the cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
126
1
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(138 citation statements)
references
References 61 publications
10
126
1
1
Order By: Relevance
“…Although a classification of the antigens detected using the sera of 18 astrocytoma patients is difficult, it is intriguing that many of them are involved in gene expression and proliferation: the son gene encodes a conserved DNA binding protein mapping to human chromosome 21; 10 the human nucleoside diphosphate kinase B, which is encoded by the gene nm23-H2, has the distinctive property of stimulating gene transcription; 11 Ranbinding protein 2, a protein containing FG repeat motifs and 4 binding sites for the guanosine triphosphatase Ran, which is localized at the cytoplasmic periphery of the nuclear pore complex, is believed to play a critical role in nuclear protein import 12 and in the nuclear export pathway; 13 and finally, BI-1, which is a regulator of cell death pathways controlled by Bcl-2 and BAX. 14 When overexpressed in mammalian cells, BI-1 suppresses apoptosis induced by Bax, etoposide, staurosporine and growth factor deprivation, but not by Fas (CD95).…”
Section: Discussionmentioning
confidence: 99%
“…Although a classification of the antigens detected using the sera of 18 astrocytoma patients is difficult, it is intriguing that many of them are involved in gene expression and proliferation: the son gene encodes a conserved DNA binding protein mapping to human chromosome 21; 10 the human nucleoside diphosphate kinase B, which is encoded by the gene nm23-H2, has the distinctive property of stimulating gene transcription; 11 Ranbinding protein 2, a protein containing FG repeat motifs and 4 binding sites for the guanosine triphosphatase Ran, which is localized at the cytoplasmic periphery of the nuclear pore complex, is believed to play a critical role in nuclear protein import 12 and in the nuclear export pathway; 13 and finally, BI-1, which is a regulator of cell death pathways controlled by Bcl-2 and BAX. 14 When overexpressed in mammalian cells, BI-1 suppresses apoptosis induced by Bax, etoposide, staurosporine and growth factor deprivation, but not by Fas (CD95).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, they are not detected in 3D reconstructions (Yang et al, 1998). Secondly, it has been shown that the Ran binding nucleoporin, Nup358, is a major constituent of the filaments (Wu et al, 1995;Delphin et al, 1997;Walther and Pickersgill et al, 2002), possibly even the filament itself, and there is apparently no similar protein in yeast. Despite the fact that Nup358 appears to be the major component of cytoplasmic filaments in the vertebrate NPC (Walther and Pickersgill et al, 2002) in yeast a similar filament structure could be constructed from one or more different proteins.…”
Section: Cytoplasmic Filamentsmentioning
confidence: 99%
“…The ring consists of at least three sequential components: (1) the star ring which lies on and is embedded in the membrane; (2) the thin ring which lies on top of the star ring and then (3) eight bipartite subunits that are molded onto the thin ring (Goldberg and Allen, 1992).The star ring has only been detected by field emission scanning electron microscopy (feSEM) (Goldberg and Allen, 1996) and may form part of the cytoplasmic ring and transmembrane vertical domains seen in 3D reconstructions (Akey and Radermacher, 1993), as the tips of its triangular shaped subunits appear to be embedded in the membrane. Filaments extend from the cytoplasmic ring into the cytoplasm and contain the Ran binding protein Nup358 (Wu et al, 1995;Delphin et al, 1997;Walther and Pickersgill et al, 2002). They appear to have controlled dynamics , but are not essential in at least some nuclear transport pathways (Walther and Pickersgill et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The filaments are composed primarily of Nup358 (12,47,50), with Nup214 and Nup88 existing as a complex on the cytoplasmic face of the NPC (3,28,39). By projecting into the cytoplasm, the filaments are in a position to interact with HSV-1 capsids.…”
mentioning
confidence: 99%